Adeno-associated viral vector delivers cardiac-specific and hypoxia-inducible VEGF expression in ischemic mouse hearts - Su, Hua (National Academy of Sciences, 2004)
It has been shown that the adeno-associated virus (AAV) vector can deliver the VEGF gene efficiently into the ischemic mouse myocardium. However, the AAV genomes can be found in extracardiac organs after intramyocardial injection. To limit unwanted VEGF expression in organs other than the heart, we tested the use of the cardiac myosin light chain 2v (MLC-2v) promoter and the hypoxia-response element to mediate cardiac-specific and hypoxia-inducible VEGF expression. An AAV vector, MLCVEGF, with 250 bp of the MLC-2v promoter and nine copies of the hypoxia-response element driving VEGF expression, was constructed. Gene expression was studied in vitro by infection of rat cardiomyocytes, rat skeletal myocytes, and mouse fibroblasts with the vector and in vivo by direct injection of the vector into normal and ischemic mouse hearts. With MLCVEGF infection, VEGF expression was higher in cardiomyocytes than the other two cell lines and was hypoxiainducible. VEGF expression was also higher in ischemic hearts than in normal hearts. No VEGF expression was detectable in organs with detectable MLCVEGF vectors other than the heart. MLCVEGF-injected ischemic hearts had more capillaries and small vessels around the injection site, smaller infarct size, and better cardiac function than the negative controls. Hence, MLCVEGF can mediate cardiac-specific and hypoxia-inducible VEGF expression, neoangiogenesis, infarct-size reduction, and cardiac functional improvement.